The Relationship Between Service Quality and Customer Green Satisfaction at Madani Hotel Medan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the relationship between service quality and customer green satisfaction at Madani Hotel Medan. The service quality in question includes aspects such as reliability, responsiveness, assurance, empathy, and physical evidence, which are integrated with environmentally friendly practices implemented by the hotel. Green satisfaction refers to the level of customer satisfaction that is not only based on conventional services, but also on the hotel's commitment to environmental sustainability. The research method used is a quantitative approach by distributing questionnaires to 100 respondents who are guests of Madani Hotel Medan. Data were analyzed using a linear regression method to determine the effect of service quality on green satisfaction. The results of the study indicate that there is a positive and significant relationship between service quality and customer green satisfaction. This finding indicates that the implementation of high-quality and environmentally friendly services can increase overall customer satisfaction. This study provides implications for hotel management to continue to improve service quality by paying attention to sustainability aspects in order to meet the expectations of increasingly environmentally conscious customers.